Composition, Antivirulence Activity, and Active Property Distribution of the Fruit of Terminalia chebula Retz. Issue 7 (17th June 2019) - Li, Kun; Han, Xianwei; Li, Ruzhuo; Xu, Zhongren; Pan, Taowen; Liu, Jing; Li, Bin; Wang, Shouyu; Diao, Yunpeng; Liu, Xinguang
Abstract : Abstract: The fruit of Terminalia chebula Retz., or Tibet Olive, is widely used as a food supplement in China. It possesses some natural antimicrobial properties; however, its chemical composition and antivirulence effects have not been identified. In this work, 29 compounds were identified from the peel of T. chebula fruit by ultra‐high‐performance liquid chromatography‐tandem quadrupole time‐of‐flight mass spectrometry. Both the extract of T. chebula and its phenolic acid, corilagin, showed antivirulent activity against Staphylococcus aureus . Specifically, they inhibited biofilm formation. The half maximal inhibitory concentration was 0.13 and 3.18 µg/mL for the extract and corilagin, respectively, whereas for α‐hemolysin secretion, the respective concentrations were 30 and 10 µg/mL. Its mechanism of action may be due to reducing the transcription of genes related to quorum sensing. These genes included staphylococcal accessory regulator A, intercellular adhesion accessory gene regulator A, and RNAIII. These findings provide evidence that this food supplement could be an effective antivirulent with corilagin as its active ingredient. Practical Application: Corilagin from the fruit of Terminalia chebula Retz. may be used as an antibacterial for its antivirulent activity against Staphylococcus aureus